Justicia espiritosantensis (Justicieae-Acanthaceae), a new species from Brazil - Aoyama, Elisa Mitsuko; Indriunas, Alexandre (Phytotaxa, 2022)
A new species, Justicia espiritosantensis, is described from Espírito Santo state, Brazil. It is closely related to J. wasshauseniana, and is distinguished from it by the plant height, peduncle length, leaf blades size, shape, venations pattern, and indument.